2011
DOI: 10.20886/jphka.2011.8.3.263-271
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Media Organik Dan Tanah Mineral Terhadap Pertumbuhan Dan Indeks Mutu Bibit Mindi

Abstract: ABSTRAKTujuan penelitian ini adalah untuk mengetahui pengaruh penggunaan campuran bahan organik dan tanah mineral sebagai media sapih terhadap pertumbuhan dan indeks mutu bibit mindi. Penelitian dilakukan di Balai Penelitian Kehutanan Ciamis pada bulan Juni 2008 s/d Januari 2009. Rancangan yang digunakan dalam penelitian ini adalah CRD (Complete Random Design) dengan tujuh perlakuan yaitu C1 (tanah + pupuk kandang (3:1)), C2 (tanah), C3 (tanah + pupuk kandang + sekam padi (1:1:1)), C4 (tanah + pupuk kandang + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
2
0
3
Order By: Relevance
“…Mindi terbukti telah dikembangkan sebagai jenis alternatif dalam pembangunan hutan tanaman di Perum Perhutani. Hal ini tentunya disebabkan prospek mindi sebagai salah satu fast growing species yang potensial dikembangkan dalam pengembangan hutan tanaman ke depan (Sudomo 2011). Mindi adalah salah satu jenis tanaman cepat tumbuh dari suku Meliaceae.…”
Section: Pendahuluan Latar Belakangunclassified
“…Mindi terbukti telah dikembangkan sebagai jenis alternatif dalam pembangunan hutan tanaman di Perum Perhutani. Hal ini tentunya disebabkan prospek mindi sebagai salah satu fast growing species yang potensial dikembangkan dalam pengembangan hutan tanaman ke depan (Sudomo 2011). Mindi adalah salah satu jenis tanaman cepat tumbuh dari suku Meliaceae.…”
Section: Pendahuluan Latar Belakangunclassified
“…This study showed that mixing peat and cocopeat, peat and compost, and peat and biochar resulted in an average DQI value of 0.10, 0.09, and 0.12. Some researchers state that seedlings are ready to be planted in the field with a DQI > 0.09 (Marjenah et al 2016;Muin et al 2022;Sudomo and Santosa 2011). Based on these standards, all growing media treatments used in this study resulted in good DQI values for preparing seedlings to be planted in the field.…”
Section: Growth Of Dyera Polyphylla and Shorea Balangeranmentioning
confidence: 77%
“…Organic matter has an important role in maintaining soil fertility, because the provision of organic material not only adds nutrients to plants, but also creates conditions suitable for plants and is able to increase the amount of water available to plants (Sudomo and Santoso, 2011). Therefore it is evident that the planting media which is only composed of soil is not good for plant growth which impacts on the G0 tubers produced.…”
Section: Resultsmentioning
confidence: 99%